Preliminary results of the morphostructural analysis of Mount Orca submarine volcano - Osses Pellegri, Gino (2019)
It is important to study in depth the morphostructural characteristics involved in underwater volcanism in order to understand the evolution of these volcanic centers with respect to their tectonic environment. Particularly, this study focuses on the Mount Orca submarine volcano, which is located at the Bransfield Strait (Antarctica), facin King George Island, and whose volcanic build reaches 650m high over a platform at 1340m deep, although the tectonic framework of the area is quite interesting, the interaction between three plates (Nazca, Scotia and Antarctic), the structural system that controls volcanism in unknown, mainly due to technological limitations or difficulty of access. This work presents a preliminary characterization of the morphology and structures associated with this underwater mount, through the digital elevation models obtained during the ANTARXXVI campaign with an EM 122 multibeam ecosystem and analyzed with CARIS Easy View and ArcMap 10.3, with the In order to identify different events and tectonic processes within the strait, their relationship with the activity of the different plates involved and how they have influenced volcanism in the area. In-depth knowledge of the morphostructural characteristics of this submarine volcano will better understand the volcanic location in the oceanic crust and its relationship with the tectonic environment.